Use Of Anthroponyms In Tahir Malik’s Stories - Rasulovna, Hamroyeva Maftuna (The journal of contemporary issues in business and government, 2021)
This article discusses the peculiarities of anthroponyms in the style of the writer, their place in the work of art. The giving of anthroponyms in creative stories is also revealed through examples.